Cognitive Ability, Character Skills, and Learning to Play Equilibrium: A Level-k Analysis - David Gill; Victoria Prowse (Institute for the Study of Labor (IZA), 2014)
In this paper we investigate how cognitive ability and character skills influence behavior, success and the evolution of play towards Nash equilibrium in repeated strategic interactions. We study behavior in a p-beauty contest experiment and find striking differences according to cognitive ability: more cognitively able subjects choose numbers closer to equilibrium, converge more frequently to equilibrium play and earn more even as behavior approaches the equilibrium prediction. To understand better how subjects with different cognitive abilities learn differently, we estimate a structural model of learning based on level-k reasoning. We find a systematic positive relationship between cognitive ability and levels; furthermore, the average level of more cognitively able subjects responds positively to the cognitive ability of their opponents, while the average level of less cognitively able subjects does not respond. Finally, we compare the influence of cognitive ability to that of character skills, and find that both cognition and personality affect behavior and learning. More agreeable and emotionally stable subjects perform better and learn faster, although the effect of cognitive ability on behavior is stronger than that of character skills.
Keywords: C92; C73; D83; 330; cognitive ability; character skills; personality traits; level-k; bounded rationality; learning; convergence; non-equilibrium behavior; beauty contest; repeated games; structural modeling; theory of mind; intelligence; IQ; cognition; Raven test